3D Finite Element Modeling of Electromagnetic Forming Processes - Bergheau, J. M.; Conraux, P.; Pignol, M.; Robin, V. (Institut für Umformtechnik - Technische Universität Dortmund, 2006)
In the electromagnetic forming process (EMF, also known as magnetic pulse forming) the metal is deformed by applying a pressure generated by an intense, transient magnetic field. A great deal of research and investigation efforts are needed for gaining better understanding on the deformation mechanism in order to develop a suitable forming strategy and equipment. One way to reach this target is to employ suitable FE software to model the process. This investigation was partly conducted in the framework of a European project called EMF (G3RD-CT-2002-00798). The first part of the paper presents the relevant physical phenomena which govern the EMF process and their interactions. The physical coupling principle as well as the required numerical models are also established. In the second section some cases for which the so developed code can be used for virtual testing is presented for validation. Finally, numerical results are compared with experiments on a 3D model, highlighting the interest of numerical modeling for process improvements.
Keywords: electromagnetic forming; finite element method (FEM); process modeling; 620; 670